Conduction of pEC22, a plasmid coding for MR.EcoT22I, mediated by a resident Tn3-like transposon, Tn5396. - Elhai, J (1994)
pEC22 is a small plasmid that encodes the restriction-modification system MR.EcoT22I. Restriction and functional analysis of the plasmid identified the positions of genes encoding that system. The plasmid is able to be conducted by conjugal plasmids, a process mediated by a transposon contained within pEC22. This cryptic transposon, called Tn5396, was isolated from pEC22 and partially sequenced. The sequence of Tn5396 is for the most part typical of transposons of the Tn3 family and is most similar to that of Tn1000. The transposon differs from closely related transposons in that it lacks well-conserved sequences in the inverted-repeat region and has an unusually long terminal inverted repeat. Consideration of regions of internal sequence similarity in this and other transposons in the Tn3 family supports a theory of the mechanism by which the ends of Tn3-like transposons may maintain substantial identity between their inverted repeats over the course of evolutionary time.